Lava Flows Erupted in 1996 on North Gorda Ridge Segment and the Geology of the Nearby Sea Cliff Hydrothermal Vent Field From 1-M Resolution AUV Mapping - Clague, David A.; Paduan, Jennifer B.; Caress, David W.; McClain, James; Zierenberg, Robert A. (Frontiers in Marine Science, 2020)
The northernmost segment of the Gorda mid-ocean ridge had a small-volume eruption in 1996 and hosts the persistent off-axis Sea Cliff hydrothermal vent field. To better understand their geologic setting and formation, 1-m resolution bathymetric mapping using autonomous underwater vehicles was completed in 2016. The mapped region covers 35 km2 and 15.6 km of the volcanic axis from south of the 1996 lava flows, and a cross section for ~4.5 km perpendicular to the axis, that extends beyond the Sea Cliff hydrothermal vent field. A proposed 1996 flow ~7 km south of previously mapped flows is an artifact from a poor pre-eruption survey. The 1996 flows consist of three discrete steep hummocky mounds of pillows and syneruptive talus. The Sea Cliff hydrothermal field is located a few km north of the narrowest, shallowest section of the ridge segment, 2.6 km east of the center of the neovolcanic zone, and ~370 m above the average depth of the axial graben on the largest offset ridge-parallel fault. No evidence supports the prior hypothesis that the site is located where two fault systems intersect. The axial graben is asymmetrical with larger fault offsets on the east side. The ridge axis below the hydrothermal field and to the south toward the 1996 flows is constructed dominantly of hummocky flows of pillow basalt, many unusually steep-sided, with syneruptive talus at the base of their steep slopes. Three channelized flows ponded between steep hummocky flows, and then partially drained. Some low-eruption-rate hummocky flows and high-eruption-rate channelized flows have nearly identical compositions, supporting the idea that eruption rates on mid-ocean ridges vary because of different dike widths. Four volcanic structures with volumes between 0.18 and 0.25 km3 occur in the axial graben south of the 1996 flows. Two are flat-topped cones, another is a 1.5-km diameter inflated hummocky flow with 7 pit craters that demonstrate that the flow had a molten interior during growth. The fourth voluminous structure is a steep ridge with abundant syneruptive talus on its lower slopes. The North Gorda segment is an end-member, structurally and volcanically, compared with other Pacific intermediate-rate spreading ridges.